Stage Migration of Metastatic Malignant Cutaneous Melanoma by 18F-FDG PET-CT Scan- A Case Report (Bangladesh Journal of Nuclear Medicine, 2022)
18F-fluorodeoxyglucose (FDG) positron emission tomographycomputed tomography (PET-CT) often causes stage migration that in turn facilitates management strategy of the diseases. This case report is an excision biopsy proven case of malignant cutaneous melanoma (malignant CM) stage pT3aN3b with clinico-pathological stage IIIC disease that was restaged to pT3aN3cM1b or stage IV disease after an 18F-FDG PET-CT scan and completely changed the therapeutic approaches. Utilization of pre therapeutic 18F-FDG PET-CT ensures appropriate staging and aids in adoption of stage appropriate management in malignant CM.Bangladesh J. Nuclear Med. 23(1&2): 51-54, 2020